Analisis Pengaruh Faktor Makro Ekonomi Terhadap Return Saham pada Sektor Properti yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017 - Daniel Phen (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The primary objective of this research is to study the influence of macroeconomic factors toward stock return of property, construction and real estate sectoral index in Indonesia Stock Exchange for 2014 until 2017. The variables for macroeconomic factors included inflation, interest rates, exchange rates, and Consumer Confidence Index. This research use multiple linear regression analysis method. The result of this research showed that inflation, interest rates, exchange rates, and Consumer Confidence Index simultaneously have significant effect toward stock returns. Partially, the research showed that only exchange rates has significant effect toward stock returns, while inflation, interest rates, and Consumer Confidence Index have no significant effect toward stock returns.